INFORMATION AS AN OBJECT OF CIVIL LAW: PROBLEMS OF UNDERSTANDING - Diduk, Alla; Lytvyn, Stepan (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose of this article is to consider problematic issues regarding the concept of information as an object of civil law, to determine the basic premises of the approach to understanding the term «information» in civil law and the legal regime of information. The term «information» is atypical for the science of law in general and civil law, in particular, because it has specific characteristics-characteristics that are not inherent in other objects of civil law. Perhaps due to this, the information still remains insufficiently researched by scholars in the field of civil law. The doctrine of civil law also lacks a generally accepted understanding of information and its legal regime. The methodological basis of the research is general scientific and special methods of scientific knowledge. The use of these methods made it possible to analyze the concept of information as an object of civil law, to consider the problems of understanding the term "information" and the legal regime of information. Results: practically all specialists in civil law in Ukraine, engaged in one way or another in the study of information as an object of law and the legislator of Ukraine, misunderstand the essence of the term "information", defining it exclusively as "information ...", at the same time as it is nothing more than a "message" (1) containing "information" (2). Discussion: the article outlines the current trends in the position and development of information law in the legislation of Ukraine, theoretical literature, different points of view of scientists regarding the concept of information, its content, trends of the problem of the legal regime of information in civil law.